Evaluation and Design Development of Rice Milling Machine - Rozi Saferi; Asmara Yanto; Zhafran Zuhairi Yodi Putra (Jurnal Teknik Mesin, 2022)
This study aims to identify and determine the level of consumer needs related to rice milling machine and, to develop a House of Quality (HOQ) to determine the dominant design requirements and the priority technical characteristics of the tool. The benefit of this research is to facilitate the design development so that it can continue to provide improvements to the quality of the rice grinder so that the quality of the rice produced can be maintained. The research method used is the Quality Function Deployment (QFD) method by conducting a survey to the field which aims to determine the level of consumer needs by distributing questionnaires and seeking information about what farmers need to make the farmer's work easier. Questionnaires were distributed to the community, most of whom work as farmers and workers in rice mills. The research location is in Pariaman Regency and Padang City. The results of this study are the highest priority scale from the aspect of consumer needs, namely fast work with a weight value (3.63) and from the technical response aspect, namely energy needs with a weight value (36.15). Based on the House of quality analysis, design development is focused on improving performance and optimizing energy sources using solar energy.